2021
DOI: 10.1186/s12864-021-07904-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide m6A profiling reveals mRNA post-transcriptional modification of boar sperm during cryopreservation

Abstract: Background Cryopreservation induces transcriptomic and epigenetic modifications that strongly impairs sperm quality and function, and thus decrease reproductive performance. N6-methyladenosine (m6A) RNA methylation varies in response to stress and has been implicated in multiple important biological processes, including post-transcriptional fate of mRNA, metabolism, and apoptosis. This study aimed to explore whether cryopreservation induces m6A modification of mRNAs associated with sperm energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 119 publications
0
24
0
1
Order By: Relevance
“…Before fertilization, both sperm cells and ova need two-stage meiosis to get haploid cells. There are a lot of factors that impact the process [10][11][12] , finally, the selection of a successful candidate should be the one with the highest percentage of physical trigonometric curves which inversion superposed by nuDNA and mtDNA from the long journey of spermatozoa with mitochondria integrated into their middle pieces. The one with a higher percentage of trigonometric curves can acquire more gravitational binding inversion energy in the journey.…”
Section: Bypassed Surface Tension Inversion (Folding) In Conventional...mentioning
confidence: 99%
“…Before fertilization, both sperm cells and ova need two-stage meiosis to get haploid cells. There are a lot of factors that impact the process [10][11][12] , finally, the selection of a successful candidate should be the one with the highest percentage of physical trigonometric curves which inversion superposed by nuDNA and mtDNA from the long journey of spermatozoa with mitochondria integrated into their middle pieces. The one with a higher percentage of trigonometric curves can acquire more gravitational binding inversion energy in the journey.…”
Section: Bypassed Surface Tension Inversion (Folding) In Conventional...mentioning
confidence: 99%
“…Bax upregulation and Bcl2 downregulation were related to enhanced apoptosis in cryopreserved mice sperm [ 110 ]. In boar, cryopreservation increased mRNA levels of FTO and decreased METTL3 , METTL14 , ALKBH5 , and YTHDF2 , which are transcripts involved in the posttranscriptional mRNA modification mediated by N6-methyladenosine [ 127 ]. In frozen–thawed bull sperm, the RPL31 gene was upregulated [ 128 ].…”
Section: Molecular Alterations In Cryopreserved Spermmentioning
confidence: 99%
“…It has been suggested that sperm RNAs are transcriptionally inactive; however, studies have shown that sperm transport specific functional RNAs into the oocyte at the time of fertilization, and these RNAs could contribute to early embryonic development [ 6 , 7 , 8 , 9 ]. Studies have demonstrated that cryopreservation has varying effects on the profiles of sperm mRNA transcripts, which could be used as markers for sperm functions [ 8 , 10 , 11 , 12 , 13 , 14 ]. Expression of PRM1 (Protamine 1) and PRM2 (Protamine 2), suggested as potential fertility markers, is significantly reduced in frozen-thawed (FT) human sperm [ 10 ], and significant changes in the mRNA expression and protein levels of epigenetic-related genes have been detected in FT boar sperm [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that cryopreservation has varying effects on the profiles of sperm mRNA transcripts, which could be used as markers for sperm functions [ 8 , 10 , 11 , 12 , 13 , 14 ]. Expression of PRM1 (Protamine 1) and PRM2 (Protamine 2), suggested as potential fertility markers, is significantly reduced in frozen-thawed (FT) human sperm [ 10 ], and significant changes in the mRNA expression and protein levels of epigenetic-related genes have been detected in FT boar sperm [ 11 , 14 ]. Evidence has shown that transcriptome modifications in FT bull sperm are associated with reduced fertility [ 12 ], and an abundance of differentially expressed (DE) genes that are highly overexpressed in FT bull sperm with poor motility [ 13 ].…”
Section: Introductionmentioning
confidence: 99%